Mediterranean fever gene variants may prevent the development of lupus nephritis in Japanese patients with systemic lupus erythematosus - Endo, Yushiro; Koga, Tomohiro; Mohamed, Lamiaa; Tsuji, Yoshika; Umeda, Masataka; Hayashi, Hiroko; Kishino, Tatsuya; Kawakami, Atsushi (Frontiers in Immunology, 2025)
BackgroundSystemic lupus erythematosus (SLE) is an autoimmune disease characterized by loss of immune tolerance, leading to systemic inflammation and organ damage. The Mediterranean fever (MEFV) gene, primarily linked to familial Mediterranean fever (FMF), has been suggested to have a protective role against SLE. However, comprehensive whole-exon analyses of MEFV and research on MEFV or FMF in non-Mediterranean populations, where MEFV exon 10 mutations are relatively rare, are limited.MethodsWe conducted a whole-exon analysis of the MEFV gene in 55 Japanese patients with SLE. Patients were classified based on the presence or absence of MEFV variants, and their clinical characteristics were compared. In addition, we generated MRL/lpr mice with the human MEFV E148Q variant using CRISPR technology to examine its impact on disease phenotypes. Disease activity and kidney pathology were assessed using the established clinical and histological scoring systems.ResultsAmong the 55 patients, those carrying MEFV variants exhibited a significantly lower prevalence of lupus nephritis than non-carriers (P = 0.007). The number of MEFV variants was inversely associated with the risk of lupus nephritis (P = 0.03). In MRL/lpr mice, the E148Q variant was associated with reduced anti-dsDNA antibody production, reduced formation of memory B cells, and milder kidney pathology, indicating a shift from adaptive immunity to innate immune responses.ConclusionsOur findings suggest that MEFV variants, particularly the E148Q variant, may play a protective role against lupus nephritis in Japanese patients with SLE by modulating immune responses. These results provide valuable insights into the genetic factors influencing SLE severity.